Interpretasi Makna Denotasi dan Konotasi dalam Lagu “Wa Ana Ma’ak” oleh Mohammed Alsahli / Interpretation of the Meaning of Denotation and Connotation in the Song “Wa Ana Ma'ak” by Mohammed Alsahli - Miftahul Mufid; M Iqbal Tawakkal; Mujahid Mujahid (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2024)
Songs often serve as a medium to express deep emotions and thoughts within our culture. Mohammed Alsahli's song